Who are the low educational achievers? : An analysis in relation to gender, emotional stability and conscientiousness - Wehner, Caroline [Verfasser]; Schils, Trudie [Verfasser] (My University, 2021)
„Low educational qualification, i.e. reaching no or only a very basic educational degree, substantially decreases an individual’s prospects on todays labour market. Emotional stability and conscientiousness are known to be predictive of educational achievement. Nevertheless, the moderating role of these two personality traits on the outcome of low educational qualification, and the interaction with gender are far less explored. In this paper, we use rich data from the British Cohort Study 1970 to analyse the relationship between personality measured in adolescence and educational achievement in adulthood. Our results show that less emotionally stable and less conscientious females have the highest risk of reaching only a low educational qualification. In contrast, more emotionally stable and less conscientious males face an above average risk of reaching a low educational qualification. Our results suggest that neglecting gender differences in the moderating relation of these two personality traits on low educational achievement is likely misleading.” (authors’ abstract; BIBB-Doku)
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 2.4.4 Biografiegestaltung; G 2.4.5 Gender Mainstreaming; G 1.3.3.1 Qualifikationsverwertung; 370; Qualifikationsniveau; Bildungsabschluss; Arbeitsmarktchance; Jugendlicher; Erwachsener; Identitätsbildung; Selbstwirksamkeit; Geschlechterdifferenz; Bildungsertrag; Großbritannien